High Level of Plasma Tumour Necrosis Factor-Î± (TNF- Î±) in Pregnant Mice Infected with Plasmodium berghei is Strongly Related to Low Level of Hemoglobin but not Related to Fetal Low Weight - Yuliyanik, Yuliyanik; Fitri, Loeki E; Sardjono, Teguh Wahju (Fakultas Kedokteran Universitas Brawijaya, 2015)
Malaria infection in pregnancy may increase the morbidity and mortality for both mother and fetus. In pregnant women, it can lead to severe anemia, cerebral malaria, pulmonary edema, renal failure and even death, while in the fetus it can cause abortion, premature birth, low birth weight, and fetal death. Elevated levels of tumor necrosis factor-Î± (TNF-Î± ) are associated with low birth weight and anemia in pregnant women. This study was conducted to measure the levels of TNF-Î± in plasma and hemoglobin levels as well as fetal weight to determine the relationship among them in P. berghei infected pregnant mice and normal pregnant mice. Seventeen BALB/c mice used in this study were divided into two groups, those were the study group (9 pregnant mice infected with P. berghei) and control group (8 pregnant mice not infected with P. berghei). Levels of TNF-Î± were measured using Enzyme Linked Immunosorbent assay (R&D Systems, catalog A00B MT). Hemoglobin levels were determined using flowcytometri, whereas fetal weights were measured with Mettler analytical balance AE 50. T-test statistical analysis showed that the levels of plasma TNF-Î± in study group were higher than control group (p=0,000). Hemoglobin levels in the study group Â were lower than control group (p=0,025). Fetal weights were also lower in fetuses of infected mice than fetuses of uninfected mice (p=0,002). Pearson correlation test showed that increasing plasma levels of TNF-Î± in infected P. berghei pregnant mice were related with the decreasing levels of Hb, (p=0,020; r=-0,748). Â However plasma levels of TNF-Î± were not associated with the incidence of fetal low weight (p=0,380, and p=0,365). It can be concluded that the increasing levels of TNF-Î± is associated with decreasing levels of hemoglobin (Hb), but not associated with fetal low weight.Keywords: Â Birth weight, hemoglobin, Plasmodium berghei, Tumour Necrosis Factor-Î± (TNF- Î±)